Critical success factors for implementing design-build: analysing Malaysian Public Projects - Lee, Zhen Ping; Rahimi, A.; Doh, Shu Ing (Emerald Publishing Limited, 2020)
The success rate of design-build (D-B) implementation in Malaysia’s private construction projects is low compared to the nation’s public projects. Thus, the purpose of this paper is to investigate the critical success factors (CSFs) for D-B implementation in Malaysian public construction projects.